Correlation Between NT-proBNP Levels And Right Ventricular Function In Patients With Pulmonary Arterial Hypertension - Yulika, Nadira Mayen; Yanni, Mefri; Adrial, Adrial (E-Jurnal Medika Udayana; Vol 14 No 7 (2025): E-Jurnal Medika Udayana, 2025)
Maladaptive pulmonary arterial hypertension (HAP) can cause changes in function in the right ventricle (VKa) due to failure to compensate for the increase in afterload over a long period of time. Changes in function in VKa can be assessed using echocardiography parameters and also biomarkers, one of which is NT- proBNP. This study aims to determine the echocardiography parameters that correlate with NT-proBNP levels in HAP patients. This will enable the assessment of VKa function in HAP patients and potentially serve as an alternative to cardiac magnetic resonance (CMR) examination, which is currently considered the gold standard for assessing RV function. This study was a cross sectional analytical study. The sample consisted of 30 patients who had been diagnosed with HAP. The analysis of bivariate data in this study used the Spearman test. The results showed that there was a moderate positive correlation between echocardiography parameters and NT-proBNP levels whose values were RVEF (r=0.372 and p=0.043), TAPSE (r=0.371 and p=0.044), FAC (r=0.377 and p=0.040), and S' (0.370 and p=0.044), respectively. In conclusion of this study was that echocardiography examination with RVEF, TAPSE, FAC, and S' parameters has a moderate correlation with NT- proBNP levels so these 4 parameters can be used as an alternative to CMR in assessing VKa function.